1990
DOI: 10.6028/jres.095.009
|View full text |Cite
|
Sign up to set email alerts
|

Observation and an explanation of breakdown of the quantum Hall effect

Abstract: We observe a spatially localized breakdown of the nearly dissipationless quantum Hall effect into a set of discrete dissipative states in wide, high-quality GaAs/AlGaAs samples. The phenomenon can be explained by an extension of the quasi-elastic inter-Landau level scattering model of Eaves and Sheard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…GaAs (8), has a zero magnetic field mobility of 100 000 cm^/(V-s) at 4.2 K, and exhibits excellent integral quantum Hall effect properties. This sample and the AT&T GaAs(7) sample used in the previous breakdown experiments [3,[5][6][7][8] have been used as the United States resistance standard.…”
Section: Samplementioning
confidence: 99%
See 2 more Smart Citations
“…GaAs (8), has a zero magnetic field mobility of 100 000 cm^/(V-s) at 4.2 K, and exhibits excellent integral quantum Hall effect properties. This sample and the AT&T GaAs(7) sample used in the previous breakdown experiments [3,[5][6][7][8] have been used as the United States resistance standard.…”
Section: Samplementioning
confidence: 99%
“…Cage et al [8] and Hein et al [9] have shown that the Vx signal can sometimes be time-averages of two or more discrete dc voltage levels in which only one level is occupied at a time, but where switching occurs between the levels. Therefore, histograms were made to ensure that the signals in n -H ,A ,A [10] , A" …”
Section: Histogramsmentioning
confidence: 99%
See 1 more Smart Citation
“…The predictions of the RK model were also verified experimentally [20,21]. Other circuit models were developed in later years [21][22][23][24][25][26][27][28] and a general method of analysis based on the indefinite admittance matrix has been recently proposed [29].…”
Section: Introductionmentioning
confidence: 85%
“…Nonetheless, a circuit model can be a useful basis for taking into account nonidealities (e.g. nonzero longitudinal resistances [24,27], parasitic elements in AC regime [41]) or to develop a SPICE macro-model, as we shall see in the next section.…”
Section: Brief Review Of Qhe Circuit Modelsmentioning
confidence: 99%